Understanding Evolving Dynamics of Scope III Emissions in the Cotton-based Textile Supply Chain in Pakistan - Kashif, Kamran (2024)
Understanding evolving dynamics of Scope III emissions which cover the significant portion of the cotton-based textile supply chain is critical for improving the sustainability performance of the textile sector. This study analyses Scope III emissions in Pakistan's cotton-based textile supply chain, focusing on farming, farm-to-ginning transport, and ginning phases.